1981
DOI: 10.1182/blood.v57.1.83.bloodjournal57183
|View full text |Cite
|
Sign up to set email alerts
|

The kidneys in paroxysmal nocturnal hemoglobinuria

Abstract: Long-term study of 21 PNH patients revealed an unexpectedly high incidence of functional and anatomic renal abnormalities. Most patients demonstrated varying degrees of hematuria and proteinuria distinct from hemoglobinuria. Evaluation of renal function revealed hyposthenuria, abnormal tubular function, and declining creatinine clearance. Radiologically these patients had enlarged kidneys, cortical infarcts, cortical thinning, and papillary necrosis which were confirmed by autopsy studies. Hypertension develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 0 publications
1
29
0
1
Order By: Relevance
“…Because of the recognized high incidence (65%) of renal dysfunction or damage at baseline in patients from the TRIUMPH study [27] and the serious and life‐threatening nature of poor renal function in patients with PNH [12], analyses were performed to assess the overall effect of eculizumab treatment on renal function. Eculizumab treatment was significantly more likely to improve CKD stage than placebo treatment through 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the recognized high incidence (65%) of renal dysfunction or damage at baseline in patients from the TRIUMPH study [27] and the serious and life‐threatening nature of poor renal function in patients with PNH [12], analyses were performed to assess the overall effect of eculizumab treatment on renal function. Eculizumab treatment was significantly more likely to improve CKD stage than placebo treatment through 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al [12] previously reported that 32% (6/19) of patients with PNH had creatinine clearance of <60 ml/min/1.73 m 2 (CKD Stages 3–5), indicating kidney damage. The exact mechanisms responsible for kidney damage in patients with PNH are unclear, but a substantial number of investigations implicate chronic hemolysis leading to hemosiderin accumulation, inflammation, and renal scarring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations